Training and Assistance in Developing Tourism Potential of Sumberdem Village as an Effort to Achieve Economic Independence - Amalia, Nasywa Putri; Nurkasanah, Ela Siti; Nabilah, Salma Haya; Harliansyah, Prastiawan; Sabrina, Diana Maulia; Suluchi, Reydi Achmad; Pransiska, Eka; Ulinnuha, Amalia Wafdana; Azzahra, Yuvy Jihan; Aulia, Najwa Syifa; Nauna, Adhwa Zahira; Sa'diyah, Halimatus; Koesuma H, Sjariefah Nayla (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This program aimed to empower the Sumberdem Village community by optimizing local potential—coffee and lemon products—through tourism development to strengthen economic independence. Method: The approach used Participatory Rural Appraisal (PRA), involving the community in mapping resources, socialization, training, mentoring, and evaluation. Activities included technical assistance for product processing, tourism management, and digital marketing strategies. Practical Applications: The program enhanced community skills in product diversification and tourism services, supported infrastructure development, and created new economic opportunities through merchandise kiosks and integrated marketing. Conclusion: PRA effectively increased community capacity and independence, strengthened village identity as an educational tourism destination, and demonstrated the potential for sustainable local economic growth.